Resource and service virtualisation in M2M and IoT platforms. (2015) - Karkazis, Panagiotis; Trakadas, Panagiotis; Zahariadis, Theodore; Chatzigiannakis, Ioannis; Dohler, Mischa; Vitaletti, Andrea; Antoniou, Athanasios; Leligou, Helen Catherine; Sarakis, Lambros
Decoupling hardware, software and service provisioning through principles of virtualisation has enabled the exponential uptake of today's internet. The currently emerging internet of things (IoT), be it through its more academic embodiment of wireless sensor networks (WSNs) or more industrial embodiment of machine-to-machine networks, is, however, still fragmented due to dispersed business models, isolated administrative control, heterogeneity of devices and platforms, proprietary communications protocols, different economic interest of stakeholders and a lack of well-crafted solutions for data, information and knowledge exchange. This work presents a novel platform supporting different aspects of WSN virtualisation to cope with requirements dictated by diverse IoT application domains. It introduces beyond state of the art technological advancements following the recent standardisation efforts in this research area. The implementation of the platform and its validation through a representative real-life application scenario exploring different virtualisation facets are also reported.